2011
DOI: 10.1080/10810730.2010.546486
|View full text |Cite
|
Sign up to set email alerts
|

Formative Research on MySpace: Online Methods to Engage Hard-to-Reach Populations

Abstract: The Internet, particularly online social networks, can be an effective and culturally relevant communications channel to engage hard-to-reach populations with HIV prevention interventions. This article describes the process of conducting formative research on a popular social networking site, MySpace, in an effort to involve youth of color in design of programmatic content and formats for an Internet intervention. We discovered that asynchronous focus groups worked well to engage hard-to-reach populations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 8 publications
1
70
0
Order By: Relevance
“…Previous nondiabetes studies have also found low response rates when recruiting young people through social network sites. 9 Levine et al, 10 for example, sought to recruit 36 young men and women from MySpace for a qualitative study and offered potential participants $25 iTunes gift certificates as incentives to take part. They sent recruitment messages directly to more than 2000 young people and had 18 responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous nondiabetes studies have also found low response rates when recruiting young people through social network sites. 9 Levine et al, 10 for example, sought to recruit 36 young men and women from MySpace for a qualitative study and offered potential participants $25 iTunes gift certificates as incentives to take part. They sent recruitment messages directly to more than 2000 young people and had 18 responses.…”
Section: Methodsmentioning
confidence: 99%
“…They sent recruitment messages directly to more than 2000 young people and had 18 responses. 10 Quantitative surveys conducted through social network sites tend not to approach potential participants directly, instead placing banner advertisements on the sites from which they are recruiting; individuals who are interested in taking part in the study can then click the advertisement, which redirects them to the survey proper. The click-through rate of these kinds of studies can be very low, in fact, much lower than traditional mail-out studies.…”
Section: Methodsmentioning
confidence: 99%
“…To address this gap, the current research leveraged SNS as an arena for generation and dissemination of UGC regarding breastfeeding. Furthermore, although increasing research has explored the potential of SNS as an effective tool for health communication (Gibbons et al, 2011;Kontos, Emmons, Puleo, & Viswanath, 2010;Levine et al, 2011;Park et al, 2013;Wright et al, 2013), there is a dearth of lab experimental research on the causal effects of Web 2.0 features and UGC in SNSs on the dynamics of persuasion. The present experimental study attempted to address these gaps by testing the persuasive effects of the interaction between UGC message styles and quantitative indicators of online popularity.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…113,127,143,144,208 Locations that are frequently accessed by the target population can be identified to maximise reach, using face-to-face methods. 118,127,153,209 This approach provides straightforward and quantifiable access where coverage and fidelity to the intervention (such as number of visits to the site and dosage) are generally higher and can be more easily measured. Nonetheless, sexual health clinic attendees also often attend on a once-only basis, limiting the opportunity for follow-up access and requiring either that interventions have impact in a single use or that ongoing online interaction is maintained.…”
Section: Clinical Settingsmentioning
confidence: 99%